Viscoelastic behavior of multiwalled carbon nanotubes into phenolic resin - Edson Cocchieri Botelho; Michelle Leali Costa; Carlos Isidoro Braga; Thomas Burkhart; Bernd Lauke (Materials Research, 2013)
Nanostructured polymer composites have opened up new perspectives for multi-functional materials. In particular, carbon nanotubes (CNTs) have the potential applications in order to improve mechanical and electrical performance in composites with aerospace application. This study focuses on the viscoelastic evaluation of phenolic resin reinforced carbon nanotubes, processed by using two techniques: aqueous-surfactant solution and three roll calender (TRC) process. According to our results a relative small amount of CNTs in a phenolic resin matrix is capable of enhancing the viscoelastic properties significantly and to modify the thermal stability. Also has been observed that when is used TRC process, the incorporation and distribution of CNT into phenolic resin is more effective when compared with aqueous solution dispersion process